Temporal and individual variation in the diet of the Neotropical otter,Lontra longicaudis(Olfers, 1818) (Carnivora, Mustelidae), as revealed by stable isotope analysis of vibrissae - Carrasco, Thayara S. [UNESP]; Lima, Renan C. de; Botta, Silvina; Machado, Rodrigo; Simoes-Lopes, Paulo C.; Ott, Paulo H.; Secchi, Eduardo R. (Springer, 2020)
The Neotropical otter,Lontra longicaudis, is a semiaquatic mustelid that preys upon fish, amphibians, and crustaceans, in variable proportions according to habitat and/or season. Due to the difficulty of observing this species in the wild, information on its ecology is typically obtained through vestiges, such as feces, which usually do not provide data at the individual level. Thus, this study aimed to assess temporal and individual variation in the diet of the Neotropical otter through chronologically ordered carbon (delta C-13) and nitrogen (delta N-15) stable isotopes data, as a proxy for dietary variation. For this purpose, isotopic values of 127 fragments of vibrissae collected from 21 individuals found dead along three coastal regions of southern Brazil were analyzed. Values ranged between - 24.0 and - 12.9 parts per thousand for delta C-13 and from 10.6 to 18.4 parts per thousand for delta N-15. Vibrissae isotopic longitudinal data were variable, indicating individual changes in the proportion of food items consumed and in foraging sites that spanned from freshwater to marine environments. Most of the populational variation in isotopic composition resulted from differences between individuals. The results of this study revealed temporal and individual variation in resource and habitat use by the Neotropical otter in three coastal ecosystems, and suggest that a high individual foraging specialization may occur in this species.
Keywords: Carbon; Feeding habits; Habitat use; Individual specialization; Nitrogen